PENGARUH VARIASI KECEPATAN DAN DIAMETER MESH TERHADAP VOLUME MADU PADA ALAT PEMERAS MADU MENGGUNAKAN MOTOR DRYER ES-T95CR DAN SPEED CONTROL - M Syifa Attamam; Retno Eka Pramitasari; Dian Anisa Rokhmah Wati; Mohammad Munib Rosadi (JOURNAL SAINS STUDENT RESEARCH, 2024)
Honey Apiss cerana It has high adaptability to local climate conditions, so this bee has received a lot of attention. Therefore, to squeeze the honey itself we still use the manual method, namely using our hands, so it is not time efficient and the sterility of the honey. method Experimental as observations made to confirm a hypothesis. To determine the effect of speed variations, namely 300 rpm, 500 rpm and 800 rpm on the resulting time efficiency then to find out the effect of variations in mesh diameters of 40 and 80 on the results of the filtering volume honey. Based on the mesh test results using mesh 1 and mesh 2, we obtained significant volume value, namely with mesh 1, the highest value is 45.7 ml, then the lowest value was 31.4 ml. With test results Kruskal Wallis namely 0.564 >0.05, the result of the speed variation is the different